HCV-RNA PCR POSITIVITY IN HCV ANTIBODY NEGATIVE PATIENTS UNDERGOING HAEMODIALYSIS - Kiani, Ismaa Ghazanfar; khan, Adil Naseer; Butt, Batool; Sabir, Sohail; Ejaz, Sundas; Perveen, Adeeba; Ghani, Ejaz (Journal of Ayub Medical College Abbottabad, 2018)
Background: It's estimated that almost 2.2% of the world's inhabitants suffer from hepatitis C virus (HCV). The most common cause of chronic liver disease in haemodialysis centres is due to HCV. In 1993, it was first described by Bukh and colleagues that HCV viremia can occur without any detectable antibodies to the HCV. Keeping this in mind the purpose of this cross-sectional study was to assess the frequency of HCV in haemodialysis patients by PCR who are serologically negative for HCV. Methods: This cross-sectional study was conducted from 1st June to 31st December 2016 on all haemodialysis patients at MH Rawalpindi. Epidemiological data for gender, age, duration on haemodialysis, cause of chronic renal failure and any associated risk factor for acquiring hepatitis C infection was asked. Patients undergoing haemodialysis were investigated by fourth generation ELISA for Anti HCV antibodies, HCV DNA polymerase chain reaction, HCV genotype (where required) and liver function test were also done. Results: A total of 201 patients were undergoing haemodialysis. Among these patients 73 were hepatitis C negative and 128 were hepatitis C positive. Among the 73 patients who were hepatitis C negative by ELISA method 17 (23%) were PCR positive. Of the 17 patients 13 (76.5%) were men and 4 (23.5%) were women. The mean age of the patients was 49.7±18.0 years and mean duration of haemodialysis was 4.4±4.1 months. The most common cause of CKD requiring haemodialysis was hypertension (64.7%). The most common genotype was type 1 (58.8%) followed by genotype 3 (41.2%). The mean viral load was 23583615.70 IU. Conclusion: HCV-RNA detection by PCR should be used as standard of care to detect HCV infection in patients undergoing haemodialysis. Keywords: End stage renal disease; hepatitis C virus; renal replacement therapy